Chnumhotep II. von Beni Hasan: Zu den letzten Kolumnen seiner Biographie - Kurth, Dieter (Zeitschrift für ägyptische Sprache und Altertumskunde, 2025)
The last columns of the famous (auto)biography of Khnumhotep II in his tomb at Beni Hasan are quite damaged and this has made their translation difficult. Based on some epigraphical corrections, a new translation and interpretation is offered which has an effect on our understanding of the design of the tomb as well as of the role of the person who was in charge of preparing the tomb for burial after its owner’s return from Abydos.